2022
DOI: 10.2196/32610
|View full text |Cite
|
Sign up to set email alerts
|

A Counseling Mobile App to Reduce the Psychosocial Impact of Human Papillomavirus Testing: Formative Research Using a User-Centered Design Approach in a Low-Middle-Income Setting in Argentina

Abstract: Background Human papillomavirus (HPV) testing detects sexually transmitted infections with oncogenic types of HPV. For many HPV-positive women, this result has negative connotations. It produces anxiety, fear of cancer or death, and disease denial. Face-to-face counseling could present many difficulties in its implementation, but a counseling mobile app could be practical and may help HPV-positive women reduce the psychosocial impact of the result, improve their knowledge of HPV and cervical cancer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…A second activity, described elsewhere, 29 was aimed at understanding women's views on an app's model called mock-up. The mock-up consisted of seven screens that included labels of the content, menus of options, and draft illustrations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A second activity, described elsewhere, 29 was aimed at understanding women's views on an app's model called mock-up. The mock-up consisted of seven screens that included labels of the content, menus of options, and draft illustrations.…”
Section: Resultsmentioning
confidence: 99%
“…The app design was based on formative research conducted among urban women living in the Metropolitan Area of Buenos Aires. The results showed that women reported unmet information needs regarding HPV and follow-up steps 29 and that is why for them the app's main objective should be to provide information on HPV, CC, and steps to follow after different HPV test results. This turned out to be the organizing axis of the design, and it became a prominent element in the different screens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations